Effect of Blood Transfusion on Short- and Long-Term Outcomes in Oral Squamous Cell Carcinoma Patients Undergoing Free Flap Reconstruction - Feng, Aimin; Zhang, Jiaqiang; Lu, Xihua; Fang, Qigen (Frontiers in Surgery, 2021)
Purpose: To analyze the short- and long-term effect of perioperative blood transfusion (PBT) in patients undergoing surgical treatment for oral squamous cell carcinoma (SCC). Methods: Patients undergoing free flap reconstruction were retrospectively enrolled and divided into two groups based on the implementation of PBT. Flap revision, surgical site infection (SSI), flap failure, overall survival (OS), and disease-specific survival (DSS) were compared between the two groups. Results: In 170 patients with PBT, 10 (5.9%) flaps required exploration revision, SSI occurred in 18 (10.6%) patients, and flap necrosis was noted in 6 (3.5%) patients. These rates were comparable to those in patients without PBT. The two groups had similar DSS rates, but the 5-year OS rates were 49% and 59% in patients with PBT and without PBT, respectively. This difference was significant. Patients with 4 units of PBT had OS rates comparable to those of patients with ＞4 units of PBT. A Cox model confirmed the fact that the decrease in OS was independent of PBT. Conclusion: In patients with free flap reconstruction for oral SCC, PBT did not increase the short-term complication rate or cancer-linked mortality. However, it was related to an elevated overall risk of death.